Changing the view: impact of simulation-based mastery learning in pediatric tracheal intubation with videolaryngoscopy - Thomaz Bittencourt Couto; Amélia G. Reis; Sylvia C.L. Farhat; Vitor E.L. Carvalho; Claudio Schvartsman (Elsevier, 2021)
Objective: To determine the effect of a training program using simulation-based mastery learning on the performance of residents in pediatric intubations with videolaryngoscopy. Method: Retrospective cohort study carried out in a tertiary pediatric hospital between July 2016 and June 2018 evaluating a database that included the performance of residents before and after training, as well as the outcome of tracheal intubations. A total of 59 pediatric residents were evaluated in the pre-training with a skills' checklist in the scenario with an intubation simulator; subsequently, they were trained individually using a simulator and deliberate practice in the department itself. After training, the residents were expected to have a minimum passing grade (90/100) in a simulated scenario. The success of the first attempted intubation, use of videolaryngoscopy, and complications in patients older than 1 year of age during the study period were also recorded in clinical practice. Results: Before training, the mean grade was 77.5/100 (SD 15.2), with only 23.7% (14/59) of residents reaching the minimum passing grade of 90/100. After training, 100% of the residents reached the grade, with an average of 94.9/100 (SD 3.2), p < 0.01, with only 5.1% (3/59) needing more practice time than that initially allocated. The success rate in the first attempt at intubation in the emergency department with videolaryngoscopy was 77.8% (21/27). The rate of adverse events associated with intubations was 26% (7/27), representing a serious event. Conclusions: Simulation-based mastery learning increased residents' skills related to intubation and allowed safe tracheal intubations with video laryngoscopy.